Enhancing lifetime of IPv6-based wireless sensor networks with address coding. (2018) - Saad, Leila Ben; Tourancheau, Bernard
Due to the scarce energy resources of sensor nodes, wireless sensor networks (WSNs) need strategies to optimise the energy consumption of sensors to extend the network lifetime. However, improving the lifetime of WSNs remains a very challenging problem. Since, a sensor device spends most of its energy in transmitting packets, it is important to shorten the length of these packets through data compression. Nevertheless, compression deals only with data while address compression is not considered. In this work, Slepian-Wolf source coding and address allocation are used jointly to reduce the size of the emitted addresses and improve the network lifetime. The proposed approach is studied in both cluster-based and multi-hop networks where two address allocation algorithms, that guarantee high correlation between addresses, are proposed. The simulation results show that a significant network lifetime improvement can be achieved by using this solution in both cluster-based and multi-hop networks.